Determinan Pemanfaatan Puskesmas pada Anak Penyandang Disabilitas - Orin Annahriyah Syukria; Stefanus Supriyanto (Indonesian Journal of Health Administration (Jurnal Administrasi Kesehatan Indonesia), 2016)
People with disability are the largest minority group. WHO informs that the group mostly stay in developing country and one third of them are children. People with disability reported to have less access to health care thancommon society. The objective of this study was to describe the factors possibly influencing the primary health care access of children with disability in Gubeng and Mulyorejo subdistrict, Surabaya, as the one of region in EastJava that reported to have not been accomodate the needs of disabled people. It was cross sectional study with observasional approach. Participants of this study were 160 children with disability along with their parents that choosen by purposive sampling. Half of population were visited and among them obtained 44 samples. The results showed that the variables significantly related to the access of primary health care were the kind of disabilty, activity of daily living value, distance between the house and health care, transportation, parents income, health cost and transportation cost. Either individual or environtmental factor could be known as thefactor that related to the access of health care in children with disability.Keywords: Activity of daily living, disability, environtmental factors, health care access